2020
DOI: 10.1002/humu.24130
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in CELF2 that disrupt the nuclear localization signal cause developmental and epileptic encephalopathy

Abstract: We report heterozygous CELF2 (NM_006561.3) variants in five unrelated individuals: Individuals 1-4 exhibited developmental and epileptic encephalopathy (DEE) and Individual 5 had intellectual disability and autistic features. CELF2 encodes a nucleocytoplasmic shuttling RNA-binding protein that has multiple roles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Indeed, our results show that individuals with perturbed CELF2 transport present with clinical features of ASD, speech delay, ID, epilepsy, and cortical malformations. During the preparation of this manuscript, an independent study (Itai et al, 2021) reported five more patients with missense (same positions also found in this study), frameshift, and splice-site variants, which similarly perturbed CELF2 transport to different degrees and caused overlapping clinical traits with varying levels of severity. This study and ours highlight an essential role of CELF2 nucleocytoplasmic shuttling in brain development and suggest that the pathological variants are likely to have an effect on additional developmental processes beyond neurogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, our results show that individuals with perturbed CELF2 transport present with clinical features of ASD, speech delay, ID, epilepsy, and cortical malformations. During the preparation of this manuscript, an independent study (Itai et al, 2021) reported five more patients with missense (same positions also found in this study), frameshift, and splice-site variants, which similarly perturbed CELF2 transport to different degrees and caused overlapping clinical traits with varying levels of severity. This study and ours highlight an essential role of CELF2 nucleocytoplasmic shuttling in brain development and suggest that the pathological variants are likely to have an effect on additional developmental processes beyond neurogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…and recruits proneural factors (such as Neurog2, Neurod1, and Tbr2) and neurodevelopmental disease-associated mRNAs into processing bodies for translational repression, thereby maintaining NPC identity and controlling the NPC fate decision (MacPherson et al, 2021). Itai et al (2021) also noticed an aberrant cytoplasmic accumulation of CELF2 after transfecting human HEK293T cells and African green monkey COS7 cells with plasmids containing disease-associated missense and frameshift variants. These results confirm the necessity of post-transcriptional regulation, and specifically of cytoplasmicnuclear shuttling activity of CELF2, for the maintenance of progenitor self-renewal properties.…”
Section: Embryonic Lethal Abnormal Vision-like and Cugbp Elavl-like Familymentioning
confidence: 97%
“…The CELF and ELAVL families are linked to neural development and as such the polymorphisms in CELF and ELAVL genes, as well as alterations in the functional properties of their respective proteins, are associated with neurodevelopmental disorders ( Popovitchenko et al, 2020 ). For example, Itai et al (2021) have identified for the first-time that heterozygous CELF2 mutations in unrelated individuals resulted in a range of overlapping clinical symptoms. These symptoms include neurodevelopmental and epileptic encephalopathy, intellectual disability, and autistic behavior – all to varying severity.…”
Section: Post-transcriptional Regulation Mrnas Poised For Translation and Rna-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…All six members have a similar structure that includes three RRMs (RNA Recognition Motifs), two in the N-terminal and one in the C-terminal, as well as a divergent linker region that can improve RBP binding affinity through conformational variations. The nuclear localization signal, which comprises a lysine/arginine-rich region in the C terminal and a region important for nuclear export in the linker domain, are two other key structures [6,13,14]. A serine/threonine-rich phosphorylation area within the CELF1 and CELF2 linker domains could change their affinity for binding to target mRNAs [15,16].…”
Section: General Characteristics Of the Celf Protein Familymentioning
confidence: 99%